Pack Carburizing Study Of Low(Mild) Carbon Steel Through Activated Carbon - Maureen, Tambi (Universiti Malaysia Sarawak (UNIMAS), 2019)
The objectives of this research are to conduct a study on the effect of pack carburizing process through activated carbon with varying time and temperature on properties of the low carbon steel sample. The properties are represented by the results of Vickers hardness testing and also the Scanning Electron Microscopy (SEM) images of the microstructure. The surface hardness of the control sample was 121 Hv. The SEM image shows the presence of pearlite which contains both ferrite and cementite. The carburizing process was conducted in three different temperatures of 850, 900 and 9509C. At each temperature, three samples were held at different carburizing times of 60, 120 and 240 minutes respectively. Once the carburizing process was accomplished, the sample was again been heated above the austenite temperature and rapidly quenched into the water bath. From the quenching process, the result shows that the sample which has been carburized at 950C and held for 240 minutes produced the highest surface hardness of 736 Hv. From the SEM images, this sample shows the highest amount of martensite (hard and brittle microstructure) was formed on its surface. All of the quenched samples then were further tempered at 550C and held for 60 minutes to reduce the brittleness. From the tempering process, the same samples produced the highest surface hardness of 411 Hv. The SEM image shows the formation of tempered martensite along with a sparsely distributed ferrite matrix. In addition, all of the results obtained was indicated a reduction in the surface hardness of all carburized tempered samples. However, the final surface hardness of all carburized samples is higher than the control sample ( 121 Hv).